Epigenetic biomarker screening by FLIM-FRET for combination therapy in ER+ breast cancer - Wenjie Liu; Yi Cui; Wen Ren; Joseph Irudayaraj (Clinical Epigenetics, 2019)
Abstract Hormone-dependent gene expression involves dynamic and orchestrated regulation of epigenome leading to a cancerous state. Estrogen receptor (ER)-positive breast cancer rely on chromatin remodeling and association with epigenetic factors in inducing ER-dependent oncogenesis and thus cell over-proliferation. The mechanistic differences between epigenetic regulation and hormone signaling provide an avenue for combination therapy of ER-positive breast cancer. We hypothesized that epigenetic biomarkers within single nucleosome proximity of ER-dependent genes could serve as potential therapeutic targets. We described here a Fluorescence lifetime imaging-based Förster resonance energy transfer (FLIM-FRET) methodology for biomarker screening that could facilitate combination therapy based on our study. We screened 11 epigenetic-related markers which include oxidative forms of DNA methylation, histone modifications, and methyl-binding domain proteins. Among them, we identified H4K12acetylation (H4K12ac) and H3K27 acetylation (H3K27ac) as potential epigenetic therapeutic targets. When histone acetyltransferase inhibitor targeting H4K12ac and H3K27ac was combined with tamoxifen, an enhanced therapeutic outcome was observed against ER-positive breast cancer both in vitro and in vivo. Together, we demonstrate a single molecule approach as an effective screening tool for devising targeted epigenetic therapy.